Class vs. field activities as supplement to the lecture-discussion method effects on achievement in high school biology - Urbiztondo, Lorna Galvan 1956- (1979)
This study was designed to evaluate field activities. Fifty second year students in Dagupan City were involved. The field activities utilized by the experimental group were gathered from unpublished research papers on ecology, written by graduates of the M.A.T. program of the UP College of Education. Based on the results of this experimental study, the use of field activities for the study of ecosystem is highly recommended. It should be a must in teaching the basic concepts of biology. Field actitivites enable students to acquire direct learning from a natural setting and involve maximum use of community resources.